Processing of liquid radioactive wastes containing organophosphorus compounds; XVI International Conference on Chemical Reactors CHEMREACTOR-16, Berlin, Germany, December 1-5, 2003 - Karpenko V. I. (2003, 2003)
Neutralization of liquid radioactive P-containing wastes of nuclear power using CaO powder as absorbent and catalyst has been studied in uniflow system. During the process all organophosphorus compounds were absorbed and converted to corrosion-inactive calcium phosphates. Radioactive elements were remained in the solid phase. Diluent hydrocarbons and organic fragments of P-containing molecules were oxidized by air to CO2+H2O. In the case of applying the additional catalytic reactor containing honecomb supported Pt catalyst the degree of neutralization of gas emissions reached 95-98 %. On the base of thermodynamic calculations and laboratory tests a technological scheme of neutralization of the radioactive liquid P-containing wastes was suggested.